Asymptotically stable solutions of a nonlinear integral equation - Özdemir, İ. (Methods of Functional Analysis and Topology, 2021)
The purpose of this paper is to study the existence and asymptotical stability of solutions of some functional integral equations which include a number of classical nonlinear integral equations as special cases. Our investigations will be carried out in the space of continuous and bounded functions on an unbounded interval. We use the technique associated with the measure of noncompactness and a suitable fixed point theorem of Darbo type. The applicability of the results is illustrated by examples showing the difference between our main result and some previous results. Метою цієї статті є дослідження існування та асимптотичної стійкості розв’язків інтегрально функціональних рівнянь, спеціальними випадками яких є низка класичних нелінійних інтегральних рівнянь. Наші дослідження ведуться в просторах обмежених неперервних функцій на нескінченному інтервалі. Використовується техніка мір некомпактності та теореми про нерухому точку типу Дарбо. Результати ілюструються прикладами, що вказують на відмінності з деякими попередніми результатами.